Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1038/jp.2012.142
|View full text |Cite
|
Sign up to set email alerts
|

Severe neonatal anemia from fetomaternal hemorrhage: report from a multihospital health-care system

Abstract: Fetomaternal hemorrhage is a rare but sometimes devastating condition. Those with fetomaternal hemorrhage and an initial Hgb of <5 g dl(-1) are expected to need resuscitation at birth, to receive emergent transfusion support and to be at risk for death and major morbidities. Antenatal suspicion of this diagnosis should occur when absent fetal movement is reported. Improvements in rapid diagnosis are needed to prepare first responders and transfusion services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 21 publications
2
42
0
1
Order By: Relevance
“…[5,12] However, even mild anemia in infancy has documented clinical significance including poor growth and cognitive deficit. [13] Despite these consequences and a suggested recent rise in incidence of severe FMH,[9] early predictors of FMH remain unknown and no cause of hemorrhage can be identified in over 80% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…[5,12] However, even mild anemia in infancy has documented clinical significance including poor growth and cognitive deficit. [13] Despite these consequences and a suggested recent rise in incidence of severe FMH,[9] early predictors of FMH remain unknown and no cause of hemorrhage can be identified in over 80% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of these pregnancies have a favorable outcome, it may be the first sign of impending fetal death or massive FMH. Despite the existence of known risk for FMH, it presents usually with nonspecific symptoms and signs such as DAFM, SHR, fetal hydrops or stillbirth [5], or early neonatal anemia [21]. If the perception of DAFM persists, consideration should be given to other causes such as fetal structural anomalies (4.3%), anemia or FMH.…”
Section: Management Of Pregnancies With Suspicion Of Clinically Relevmentioning
confidence: 99%
“…Christensen et al [21] have performed multicentered data-based study on 219 853 live births and identified all anemic neonates with either hematocrit less than 30% or hemoglobin less than 10 g/dl on the day of birth, who had laboratory-based…”
Section: Massive Fetomaternal Hemorrhagementioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective studies in large populations document an incidence of FMH diagnosis of 1–2/10,000 live births. [4, 5, 10] The true incidence of clinically significant FMH is likely much higher, however, as FMH testing is underutilized in clinical practice. [4, 5, 11] Currently, testing for FMH after live birth occurs when significant fetal or neonatal anemia or is recognized.…”
Section: Introductionmentioning
confidence: 99%